Sociedade, tecnologias e educação: as tecnologias da informação e comunicação e o pensar da sociedade concreta - Cruz, José Anderson Santos [UNESP]; Bizelli, Jose Luis [UNESP] (Brazilian Journal of Education, Technology and Society (BRAJETS), 2014)
The information society is increasingly incorporating the immense volume of content available on the net. Access by electronic devices and the resulting ease of mobility and portability feed discussions on actual capacity of appropriation of this knowledge that circulates through cyberspace. Address and discuss the possibilities of educating across the network, therefore, gains more and more importance. On models of educational quality well developed – as is the case in Finland, for example-, Brazilian education is, year after year, failing in international marathons to achieve below average indexes required. Creates a field of analysis, in which this article arises, in the quest to understand more deeply the opportunity of use of Information and communication technologies (ICT) for a quality education, plunging by cultural issues that fall in the construction of objective conditions offered to students. This is an effort in understanding the historical factors that limit efforts to offering a quality education in Brazil.

A sociedade da informação está cada vez mais incorporando o imenso volume de conteúdos disponíveis na rede. O acesso por dispositivos eletrônicos e a facilidade resultante da mobilidade e da portabilidade alimenta discussões sobre a capacidade real de apropriação desse conhecimento que circula pelo ciberespaço. Abordar e discutir as possibilidades de educar pela rede, portanto, ganha cada vez mais relevância. Diante de modelos de qualidade educativa bem desenvolvida – como acontece na Finlândia, por exemplo –, a educação brasileira vai sendo, ano a ano, reprovada nas maratonas internacionais por atingir índices abaixo da média exigida. Cria-se um campo de análise, no qual este artigo se coloca na busca por entender mais profundamente a oportunidade de utilização das Tecnologias de Comunicação e Informação (TIC) para uma educação de qualidade, mergulhando pelas questões culturais que se inserem na construção das condições objetivas oferecidas aos educandos brasileiros. Trata-se de um esforço na compreensão dos fatores históricos que limitam os esforços para o oferecimento de uma educação de qualidade no Brasil.
Society, technology and education: information and communication technologies and the thinking of the concrete society
Keywords: Education; ICT; The information and knowledge society; Structural Limits; Educação; Educação a distancia; TIC; Sociedade do conhecimento